A family apart. The crisis of the family in postmodernity - Lubowicka, Grażyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
A crisis of values and pluralism in postmodern society have led to the family no longer being considered an essential value or an element of an unalterable social order. Individualistic attitude of postmodern man focused on self-realisation implied that the family should bring personal fulfilment, as well as satisfaction and pleasure. Frail human bonds, in particular, unstable intimate relationships, are changing the family into a contract between free partners, a deal or a transaction that should provide for emotional and spiritual needs of the contracting parties.
Keywords: family; crisis of values; pluralism; individualism; postmodernity